2020
DOI: 10.1109/access.2020.3019048
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Network Architecture of Decision-Making for Self-Driving Vehicles Based on Long Short-Term Memory and Grasshopper Optimization Algorithm

Abstract: Long short-term memory network is one of the most important network architectures of decision-making for self-driving vehicles. Nevertheless, the decision-making accuracy of long short-term memory network is limited, the information of the surrounding vehicles is not taken into consideration, which is critical for the decision-making of the ego vehicle, and the classification capability of long shortterm memory network is poor. In this paper, a novel network architecture called improved long short-term memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Another similar work was done by Barman et al [73] and Ibrahim et al [135]. Shi et al [136] suggested an improved long short-term memory GOA (GOA-ImLSTM) by hybridizing GOA with SVM and LSTM for decision-making for Self-Driving Vehicles. GOA-ImLSTM was assessed using Vehicle trajectory data collected from Roads of Los Angeles and California.…”
Section: ) Hybridization With Invasive Weed Optimization Algorithmmentioning
confidence: 92%
See 1 more Smart Citation
“…Another similar work was done by Barman et al [73] and Ibrahim et al [135]. Shi et al [136] suggested an improved long short-term memory GOA (GOA-ImLSTM) by hybridizing GOA with SVM and LSTM for decision-making for Self-Driving Vehicles. GOA-ImLSTM was assessed using Vehicle trajectory data collected from Roads of Los Angeles and California.…”
Section: ) Hybridization With Invasive Weed Optimization Algorithmmentioning
confidence: 92%
“…Content may change prior to final publication. [122] hybrid-GOA-GA [123] GOA-jDE [124] DE-GOA-KELM [125] HAGOA [126] GWGHA [127] BGOA [128] HGOA [129] SM-GNCSOA [130] GOALO [131] HAGOA [132] TLGOA [133] IWGOA [128] GOA-SVR [134] GOA-SVM [72] GOA-SVM [73] GOA-SVM [135] GOA-ImLSTM [136] GOA-MSVM [137] GOA-SVM [138] GOA was proposed by hybridizing GOA with GWO for tackling the text feature selection problem. GWO-GOA was assessed using eight datasets taking into account five metrics (i.e accuracy, sensitivity, specificity, precision, recall, and F-measure).…”
Section: ) Hybridization With Grey Wolf Optimizermentioning
confidence: 99%
“…In order to avoid similar problems, LSTM as a specific RNN network model can solve the problem of a long-term dependence on historical information, so that based on directional selection and reasonable inheritance of current and historical information, it can complete information identification at the current time [33] and feature extraction [34] and information prediction at the next time [35] by comprehensively considering the role of historical input information. The main research content of this paper is based on the vehicle dynamic state information such as lateral acceleration, yaw rate, and tire force in the optimized time-domain length, and the LSTM network is adopted to extract the data features under the input state and predict the calculation to obtain the future sideslip angle of the center of mass.…”
Section: Prediction Network Construction Based On Lstm Networkmentioning
confidence: 99%
“…NGSIM does not contain vehicle steering angle information. Horizontal and vertical coordinates of three consecutive moments of the vehicle are used to calculate the steering angle [29]. The steering angle is calculated as follows.…”
Section: A Dataset and Processingmentioning
confidence: 99%
“…Learning multiple sets of images through LSTM improved the accuracy of corner controlling. Shi et al [29] proposed a model of three parallel LSTM and one LSTM in series. The model extracted features by different lanes.…”
Section: Introductionmentioning
confidence: 99%